THE PSYCHOLOGICAL DETERMINANTS OF LONG DISTANCE RUNNERS PERFORMANCE - Rehan Yousaf; Jamshaid Ahmad; Sumaira Sarwar (The Sky, 2017)
Generally the performance of the long distance runners is not progressing in Pakistan. There is lack of awareness of modern sports techniques in Pakistan to improve the abilities of a long distance runner. Psychological determinants can play a very important role to identify the weaknesses and strengths of the athletes. This study is helpful to understand the importance of different psychological determinants such as sports motivation, mental toughness and sports confidence in relation to performance. The long distance 83 athletes were selected from Punjab, Pakistan having average age of 27 years. Adopted questionnaire was used to collect the survey data. Findings of the study show that there is high positive and significant effect of sports confidence and sports motivation on sports performance while mental toughness effects negatively but significantly on sports performance. On the basis of these results, the study will help coaches for the psychological training of long distance runners which may enhance their performance in practice as well as in the competitions.